2020
DOI: 10.1007/s12325-019-01211-1
|View full text |Cite
|
Sign up to set email alerts
|

Critical Differences Between Dietary Supplement and Prescription Omega-3 Fatty Acids: A Narrative Review

Abstract: Introduction: Currently available omega-3 (OM-3) fatty acid products in the US are either nonprescription dietary supplements (e.g., fish oils) or prescription (Rx) medications. As such, we aimed to describe critical therapeutic differences among the OM-3 fatty acids, focusing on differences between fish oil supplements and Rx OM-3s. Methods: A narrative review of known papers salient to this topic was conducted. Results: Despite the multiple purported clinical benefits, the published evidence for OM-3 dietary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 51 publications
0
27
0
Order By: Relevance
“…This metabolic switch in WAT lowers triglycerides and induces mitochondrial biogenesis [ 27 ]. Fish oil mainly reduces triglycerides and inflammation, but the results have been variable [ 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…This metabolic switch in WAT lowers triglycerides and induces mitochondrial biogenesis [ 27 ]. Fish oil mainly reduces triglycerides and inflammation, but the results have been variable [ 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…The VITAL trial using one-fourth of the dose of combined EPA + DHA esters we employed did not show evidence of prevention of cancer or cardiovascular disease [49]. However, the dose in the VITAL trial likely produced only a fraction of systemic levels obtained in animal studies where cancer preventive effects were observed [17,18,23] different CVD outcomes in ω-3-FA arms for the ASCEND (0.84 g total DHA + EPA/day) vs REDUCE-IT trials (4 g EPA/day) [50].…”
Section: Discussionmentioning
confidence: 94%
“…2,3,21 However, the historical uncertainty surrounding the actual clinical evidence base for the efficacy of omega-3 fish oils has severely curtailed their clinical role. Hence, clinical interest is likely to stay focused on adjunctively harnessing the ability of prescription omega-3 acid ethyl esters (as medicinal products distinct from dietary omega-3 fish oil supplements 15,35,36 ) to lower elevated triglycerides in the overall management of residual cardiovascular risk.…”
Section: Discussionmentioning
confidence: 99%